Evaluation of dentoalveolar and temporomandibular joint injuries during endotracheal intubation: a survey study - Çakmakoğlu, Ezgi Eroğlu; Çelebi, Adalet; Kızılkaya, Ayşe Rençber; Açıkyol, Gamze; Kucuk, Ayse Ozcan; Doruk, Nurcan; Atıl, Fethi (My University, 2025)
Aims: Endotracheal intubation is a widely utilised technique in the fields of anesthesia and resuscitation. However, dentoalveolar and temporomandibular joint (TMJ) injuries may occur frequently during this procedure. Such injuries can result in patient morbidity and, in some cases, may also give rise to medico-legal issues. It is therefore essential to develop a comprehensive understanding of the prevalence of such injuries, the risk factors that contribute to their occurrence, and effective management strategies to minimize the likelihood of these complications arising. Methods: A cross-sectional study was conducted to evaluate the knowledge and attitudes of 227 anesthesiologists across Turkiye regarding dentoalveolar and TMJ injuries occurring during endotracheal intubation. A previously validated online questionnaire consisting of 20 questions was administered. Data were analyzed with IBM SPSS v23 software, and the significance level was evaluated as p<0.05 using Fisher’s exact test with Monte Carlo correction between categorical data. Results: The survey revealed that 67.4% of the participants reported cases of dental trauma in adult patients, with a smaller percentage (28.2%) reporting cases in pediatric patients. The survey also revealed that the use of protective devices was minimal, with only 5.3% of participants reporting their use. However, a significant proportion (93%) of the participants stated that education should be provided on the prevention and management of dental trauma. The most common site of injury was the anterior teeth of the maxilla (82.8%), and the most common type of trauma was tooth fracture (56.6%). Furthermore, temporomandibular joint dislocation was reported in 26.4% of participants during the intubation process. Conclusion: Dentoalveolar and TMJ injuries during endotracheal intubation are a prevalent yet under-researched problem. This study underscores the necessity for training programmes to formulate preventive measures and emergency intervention methods. Preoperative dental assessments and the utilization of protective devices can markedly reduce the incidence of such injuries.
Keywords: Survey; endotracheal intubation; Dentoalveolar injuries; temporomandibular joint injuries